Effect of Biochar Application Depth on a Former Mine Technosol: Impact on Metal(Loid)s and Alnus Growth - Gloria Palmeggiani (MDPI AG, 2021)
The contamination of soil by potentially toxic elements (PTEs) is a problem resulting from various anthropic activities including the exploitation of mines, which determines an accumulation of metal(loid)s in the surrounding area. It is therefore necessary to use remediation techniques to prevent the potential damage to human health and the ecosystem. One of these techniques is phytoremediation, which involves the revegetation of contaminated areas in such a way as to reduce the spread of contaminants and entry into the groundwater by stabilizing the metal(loid)s in the soil, decreasing their mobility. To increase the ability of plants to grow under the extreme conditions of contaminated soils, it is necessary to use amendments, which can also intervene directly in reducing the mobility of contaminants. In this study, an open-field mesocosm was set up using a former mining technosol contaminated mainly by As. A biochar produced from hardwood was added at two different depths to evaluate the effectiveness of these application modalities for an overall observation duration of 17 months. Iron sulphate was also applied in both non-biochar and biochar amended conditions. In addition, trees of Alnus sp. were planted to examine the effectiveness of these plants for their use in soil remediation and the effect of the treatments used. The results showed an increase in soil pH induced by the biochar, which decreased over time. During the period examined, the application of biochar in the deepest layer was able to retain As more effectively. The Alnus sp. showed similar growth rates among the various treatments, resulting from its tolerance towards arsenic.